2010
DOI: 10.1002/pros.21172
|View full text |Cite
|
Sign up to set email alerts
|

Targeting tumor metabolism with 2‐deoxyglucose in patients with castrate‐resistant prostate cancer and advanced malignancies

Abstract: BACKGROUND A profound difference between cancer and normal tissues is the preferential utilization of glycolysis by cancer cells. To translate this paradigm in the clinic, we completed a phase I study of 2-deoxyglucose (2DG), and assessed 2DG uptake with fluorodeoxyglucose (FDG) positron emission tomography (PET) and the autophagy substrate p62 as a marker of 2DG resistance. METHODS Patients received 2DG orally on days 1–14 of a 21-day cycle in cohorts of three in a dose-escalating manner. Correlative assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
218
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(232 citation statements)
references
References 24 publications
5
218
0
1
Order By: Relevance
“…Our study suggests that such cotreatment might be efficient not only by increasing the cytotoxicity of the chemotherapy but also by allowing the immune system to react against the tumor. It is interesting to note that the dose of 2DG used in our study is equivalent to the one shown to be safe in human clinical trials (23,24).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our study suggests that such cotreatment might be efficient not only by increasing the cytotoxicity of the chemotherapy but also by allowing the immune system to react against the tumor. It is interesting to note that the dose of 2DG used in our study is equivalent to the one shown to be safe in human clinical trials (23,24).…”
Section: Discussionmentioning
confidence: 86%
“…3 and 6). Several reports have indicated that 2DG administrated orally was safe and well tolerated by patients (23), leading to the launch of several phase II and III clinical trials in cancer therapy. Our study suggests that such cotreatment might be efficient not only by increasing the cytotoxicity of the chemotherapy but also by allowing the immune system to react against the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, high grade (Gleason > 7) and castration-resistant tumors seem to reactivate glycolysis, since FDG-PET and FDG-PET/CT studies indicate an increased glucose uptake compared to benign and low stage prostate cancers [153][154][155][156][157]. Accordingly, prostate cancer is affected by 2-deoxyglucose [158][159][160]. This is further in agreement with cell line studies, which show that the metastastic androgen-sensitive cell line LNCaP and the castration-resistant low-differentiation cell lines DU-145 and PC-3 are sensitive to glucose starvation [152] and that androgen signaling enhances the expression of glycolytic enzymes [161][162][163].…”
Section: Later Stage Prostate Cancer Metabolismmentioning
confidence: 99%
“…These enzymes in gluconeogenesis, namely phosphoenolpyruvate carboxykinase (PEPCK), fructose-1,6-bisphosphatase and glucose-6-phosphatase (G6Pase), convert oxaloacetate to phosphoenolpyruvate, fructose 1,6-bisphosphate to fructose 6-phosphate and glucose-6-phosphate to glucose, respectively, leading to an effective reversal of glycolysis [4][5][6] . Recently, metabolism of glucose by cancer cells has been intensively studied and targeting tumour metabolism is highlighted as a potential strategy against cancer [7][8][9][10] . However, how and whether gluconeogenesis affects tumour metabolism remains unclear.…”
mentioning
confidence: 99%